Current Strategies for the Management of Painful Diabetic Neuropathy. (March 2022) - Staudt, Michael D.; Prabhala, Tarun; Sheldon, Breanna L.; Quaranta, Nicholas; Zakher, Michael; Bhullar, Ravneet; Pilitsis, Julie G.; Argoff, Charles E.
The development of painful diabetic neuropathy (PDN) is a common complication of chronic diabetes that can be associated with significant disability and healthcare costs. Prompt symptom identification and aggressive glycemic control is essential in controlling the development of neuropathic complications; however, adequate pain relief remains challenging and there are considerable unmet needs in this patient population. Although guidelines have been established regarding the pharmacological management of PDN, pain control is inadequate or refractory in a high proportion of patients. Pharmacotherapy with anticonvulsants (pregabalin, gabapentin) and antidepressants (duloxetine) are common first-line agents. The use of oral opioids is associated with considerable morbidity and mortality and can also lead to opioid-induced hyperalgesia. Their use is therefore discouraged. There is an emerging role for neuromodulation treatment modalities including intrathecal drug delivery, spinal cord stimulation, and dorsal root ganglion stimulation. Furthermore, consideration of holistic alternative therapies such as yoga and acupuncture may augment a multidisciplinary treatment approach. This aim of this review is to focus on the current management strategies for the treatment of PDN, with a discussion of treatment rationale and practical considerations for their implementation.